Potential Target Analysis of Triptolide Based on Transcriptome-Wide m6A Methylome in Rheumatoid Arthritis - Fan, Danping; Liu, Bin; Gu, Xiaofeng; Zhang, Qian; Ye, Qinbin; Xi, Xiaoyu; Xia, Ya; Wang, Qiong; Wang, Zheng; Wang, Bailiang; Xu, Yuan; Xiao, Cheng (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a complicated autoimmune disease affected by various factors such as epigenetics. N6-methyladenosine (m6A) is the most abundant post-transcriptional modification of eukaryotic mRNA, and plays important role in RA pathological process. However, the regulatory mechanism of m6A in RA has not been fully elucidated. This study is to assess the m6A methylome in the RA peripheral blood mononuclear cells (PBMCs) and perform potential drug targets prediction analysis. Five RA samples and ten control samples were obtained from China-Japan Friendship Hospital. m6A modifications with methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) were performed to compare the differential expression of m6A methylation and genes in RA and control group. Bioinformatics analyses were also conducted to explore the enriched biological functions and pathways of the differentially expressed m6A methylation and genes. Potential drug targets prediction and validation were also constructed to provide potential therapeutic targets for RA. In total, 583 dysregulated m6A peaks, of which 295 were significantly upregulated and 288 were significantly downregulated, were identified. Likewise, 1570 differentially genes were obtained by RNA-seq, of which 539 were upregulated and 1031 downregulated. Further joint analysis showed that the m6A methylation and mRNA expression levels of 35 genes changed significantly, of which including 13 hyper-methylated as well as upregulated genes (hyper-up), 12 hyper-methylated as well as downregulated genes (hyper-down), 5 hypo-methylated as well as upregulated genes (hypo-up), and 5 hypo-methylated as well as downregulated genes (hypo-down) GO and KEGG analyses indicated that these unique genes were mainly enriched in “protein transport” “protein binding” and “lysosome”. In addition, the mRNA levels of TUBB2A, IGF2BP3, DYNC1I1 and FOSL1 were increased and consistent with the trend of our sequencing results. While after the treatment of TP and MTX, their mRNA levels were decreased. This study established the transcriptional map of m6A in RA PBMCs and revealed the potential relationship between RNA methylation modification and related genes in RA. The results highlight the importance of m6A modification as a gene regulatory system in RA. Furthermore, TUBB2A, IGF2BP3, DYNC1I1 and FOSL1 might be potential therapeutic targets of TP and MTX during RA treatment.